Activity of the UN Security Council Committee on the Prevention of Proliferation of Weapons of Mass Destruction - T. N. Voytova (Московский журнал международного права, 2011)
The article is concerned about analysis of activity of United Nations Security Council Committee established pursuant to resolution 1540 (2004). Committee monitors implementation of legislative resolution 1540 (2004) dealing with prevention of proliferation of weapons of mass destruction, their means of delivery and related materials by non-state actors. The article provides characteristic of structure and main areas of activity of Committee 1540 such as the examination of relevant measures taken by State Members of the United Nations, the organization of intensive outreach activities, the development of cooperation with other Security Council bodies and with global, regional and sub regional intergovernmental organizations, the creation of new tools to facilitate assistance and transparency. The accent is made on characteristic of current general trends in the Member State’s implementation of resolution 1540 (2004) and main priorities of future work of Committee 1540.